2016
DOI: 10.1364/oe.24.002590
|View full text |Cite
|
Sign up to set email alerts
|

Silicon carbide—a high-transparency nonlinear material for THz applications

Abstract: Optical properties of 4H-SiC were measured using time-domain and Fourier transform spectroscopy in the range of 0.1-20 THz. A high-transparency region was found between <0.1-10 THz. Based on the obtained data and published results, the refractive indices for o-wave and e-wave were approximated in the form of Sellmeier equations for the entire transparency range. Phase matched frequency conversion was found to be possible at wavelengths from the visible through the mid-IR and further into the far-IR (THz) regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…These refractive index dispersions differ slightly from previously reported values [16] and provide a better description of the phase-matching conditions that we observe. Phase-matching angles based on the refractive index data have been calculated for pump wavelength λ p and target idler emission wavelength λ i of the DFG process.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…These refractive index dispersions differ slightly from previously reported values [16] and provide a better description of the phase-matching conditions that we observe. Phase-matching angles based on the refractive index data have been calculated for pump wavelength λ p and target idler emission wavelength λ i of the DFG process.…”
supporting
confidence: 49%
“…Furthermore, organic nonlinear crystals [15] show heavily structured spectra in the frequency range of interest and display inherently low damage thresholds. Recently, preliminary investigations by Naftaly et al [16] suggested 4H-SiC as a crystal suitable for nonlinear optics in the multi-terahertz range. So far, this outstanding material has received little attention in experimental works that are limited to the demonstration of nonlinear properties in the near infrared [17], mid-infrared DFG above the optical phonon frequencies [18], and emission of 1 THz radiation from 6H-SiC [19].…”
mentioning
confidence: 99%
“…The THz temporal profile can be measured with 10 fs timing resolution and covers the spectral range from 37 to 3000 mm (0.1 to 8 THz). The ongoing development of this technique will explore the use of different EOS crystals to extend the measured bandwidth to shorter wavelengths, GaSe (Kü bler et al, 2005) and SiC (Naftaly et al, 2016) being good candidates that should allow THz detection in the 10-40 THz and 0.1-15 THz spectral windows, respectively. To fully exploit the high THz pulse energies at FLASH, we are upgrading the single-shot EOSD THz detection technique to one via tilted laser pulse front (Teo et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, organic nonlinear crystals [15] show heavily structured spectra in the frequency range of interest and display inherently low damage thresholds. Recently, preliminary investigations by Naftaly et al [16] suggested 4H-SiC as a crystal suitable for nonlinear optics in the multi-terahertz range. So far, this outstanding material has received little attention in experimental works that are limited to the demonstration of nonlinear properties in the near infrared [17], mid-infrared DFG above the optical phonon frequencies [18], and emission of 1 THz radiation from 6H-SiC [19].…”
mentioning
confidence: 99%